(3x+1)*(4x-4)=0

Simple and best practice solution for (3x+1)*(4x-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+1)*(4x-4)=0 equation:



(3x+1)(4x-4)=0
We multiply parentheses ..
(+12x^2-12x+4x-4)=0
We get rid of parentheses
12x^2-12x+4x-4=0
We add all the numbers together, and all the variables
12x^2-8x-4=0
a = 12; b = -8; c = -4;
Δ = b2-4ac
Δ = -82-4·12·(-4)
Δ = 256
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{256}=16$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-8)-16}{2*12}=\frac{-8}{24} =-1/3 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-8)+16}{2*12}=\frac{24}{24} =1 $

See similar equations:

| 2(7+3m)=5(2m-3)-m | | (x+2)÷6=(2x-10)÷8 | | -1-4x=6x+5 | | 4=f/2—-3 | | Y=2x+4=42-7x | | 5h+3h=8 | | 3b+10=56 | | 3(3x-+5)-4x=3x-10 | | 5+6x=-2x+10-45 | | 4(2x+1)=22+3 | | 9p+3+6p=-16+14p | | -(x+7)=-23 | | 7r+6=4r | | 6d−–3=21 | | 14-2y=5y | | 1/4p-6=5 | | 3(x+8)=2(2x+7) | | 2+-z=7 | | 3.2x(2.3–0.5)= | | -55+3x=85-x | | 12−0.8(x+15)=0.4x+6 | | -7x-5=-10x+26 | | 2x3-3x2=0 | | 14x-31=12x+47 | | 2x+39+1+90=180 | | 10x=560 | | 6x-9-9x=15+4x-3x | | –2u−7=–u | | (x+40)+(3x-80)=180 | | 12x-29=10x-19 | | 5+3|10−4x|=20 | | 2(x-1)+6=3+2x-10 |

Equations solver categories